Factors that influence tax auditors' conciliatory style in resolving disputes: Pre-test and pilot study - Nordin, ZS; Muhammad, I (Univ Utara Malaysia,Tunku Puteri Lntan Safinaz Sch Accountancy (Tissa), 2024)
Indexed by WOS